2006
DOI: 10.1086/498446
|View full text |Cite
|
Sign up to set email alerts
|

Binary Mergers and Growth of Black Holes in Dense Star Clusters

Abstract: We model the dynamical evolution of primordial black holes (BHs) in dense star clusters using a simplified treatment of stellar dynamics in which the BHs are assumed to remain concentrated in an inner core, completely decoupled from the background stars. Dynamical interactions involving BH binaries are computed exactly and are generated according to a Monte Carlo prescription. Recoil and ejections lead to complete evaporation of the BH core on a timescale ~10^9 yr for typical globular cluster parameters. Orbit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
305
4

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(332 citation statements)
references
References 60 publications
23
305
4
Order By: Relevance
“…Another model [26] studies the progressive accumulation of mass into a large (> 50 M ) seed black hole via coalescence of a population of smaller black holes. However, the existence of binaries with IMBH components remains uncertain since stellar winds may stall the growth of the IMBH progenitors in the runaway collision scenario [27], or the merger recoil may also eject a newly formed black hole from the globular cluster [28,29].…”
Section: A Intermediate Mass Black Hole Formationmentioning
confidence: 99%
“…Another model [26] studies the progressive accumulation of mass into a large (> 50 M ) seed black hole via coalescence of a population of smaller black holes. However, the existence of binaries with IMBH components remains uncertain since stellar winds may stall the growth of the IMBH progenitors in the runaway collision scenario [27], or the merger recoil may also eject a newly formed black hole from the globular cluster [28,29].…”
Section: A Intermediate Mass Black Hole Formationmentioning
confidence: 99%
“…However, Advanced LIGO can only detect mergers that occurred at distances P1 Gpc, i.e., relatively recently, so the relevant rate is the rate late in the history of the globular cluster, which is likely to be much lower. For example, O'Leary et al (2006) found in their numerical simulations that the rate dropped from $10 À7 to $3 ; 10 À10 yr À1 after 10 10 yr for some plausible cluster models.…”
Section: Imri Rate Per Globular Cluster and Event Ratementioning
confidence: 99%
“…Although the predicted formation rate of merging double NSs has a strong density dependence (Ivanova et al 2007), even for dense clusters like 47 Tuc the NS contribution to total cluster merger rates should be overwhelmed by double BH mergers. Such systems are expected to be formed via dynamical interactions in cluster cores (Gultekin et al 2004;O'Leary et al 2006O'Leary et al , 2008. O'Leary et al (2006O'Leary et al ( , 2008 used realistic initial conditions for their cluster simulations (which included the stellar evolution of massive stars and binaries in the first few Myr of the cluster life) and assumed immediate creation of a BH subcluster.…”
Section: Introductionmentioning
confidence: 99%
“…Such systems are expected to be formed via dynamical interactions in cluster cores (Gultekin et al 2004;O'Leary et al 2006O'Leary et al , 2008. O'Leary et al (2006O'Leary et al ( , 2008 used realistic initial conditions for their cluster simulations (which included the stellar evolution of massive stars and binaries in the first few Myr of the cluster life) and assumed immediate creation of a BH subcluster. Their calculations did not consider further stellar or binary evolution and neglected the effects of lower mass stars on BH populations.…”
Section: Introductionmentioning
confidence: 99%